2015
DOI: 10.3390/ijms160921070
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Lanthanum-Incorporated Hydroxyapatite Coatings on Titanium Substrates

Abstract: Titanium (Ti) has been widely used in clinical applications for its excellent biocompatibility and mechanical properties. However, the bioinertness of the surface of Ti has motivated researchers to improve the physicochemical and biological properties of the implants through various surface modifications, such as coatings. For this purpose, we prepared a novel bioactive material, a lanthanum-incorporated hydroxyapatite (La-HA) coating, using a dip-coating technique with a La-HA sol along with post-heat treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…Incorporation of 10 wt.% and 20 wt.% of B 2 O 3 in HA showed slightly toxic effect. It was reported that incorporation of La 3+ increased the proliferation rate of MC3T3-E1 cells [18,55]. For all composites, a time-dependent decrease in the cell viability was observed.…”
Section: In Vitro Cytotoxicity Evaluationmentioning
confidence: 74%
See 3 more Smart Citations
“…Incorporation of 10 wt.% and 20 wt.% of B 2 O 3 in HA showed slightly toxic effect. It was reported that incorporation of La 3+ increased the proliferation rate of MC3T3-E1 cells [18,55]. For all composites, a time-dependent decrease in the cell viability was observed.…”
Section: In Vitro Cytotoxicity Evaluationmentioning
confidence: 74%
“…Lattice parameters of the pure HA and HA-B 2 O 3 -La 2 O 3 composites are summarized in Table 2 and the lattice values were in good agreement with dimensions of hexagonal structure of HA. Few variations in a and c axis of HA-B 2 O 3 -La 2 O 3 composites could be attributed to the dehydroxylation of the hydroxyl group which is very common for the samples calcined at high temperatures [34] or due to the partial substitution of a smaller radius Ca 2+ (0.99 Å) with a larger radius La 3+ ion (1.17Å) [18]. However, the addition of both B 2 O 3 and La 2 O 3 into HA did not result in significant changes in XRD patterns of the HA as they were still matched with the standard JCPDS file for HA.…”
Section: Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…La2O3 merupakan oksida logam yang sering digunakan pada aplikasi biomedis karena tidak beracun, tidak menyebabkan iritasi, tidak menyebabkan sensitifitas terhadap sel tubuh, tidak memiliki toksisitas akut dan tidak bepotensi untuk terjadinya mutasi (Brabu et al, 2014). Pada penelitian lainnya komposit HA dengan lantanum oksida tidak beracun pada jaringan tulang dan mampu meningkatkan sifat biologisnya yang ditunjukkan rendahnya tingkat disolusi terhadap asam (Lou et al, 2015). Menurut Gerber et al, (2012) (Lim, 2015).…”
Section: Pendahuluanunclassified